Pengaruh Bystander Effect, Financial Attitude dan Modal Sosial Terhadap Upaya Pencegahan Fraud Pengelolaan BUMDES - Parmin Ishak; Fitrianti Fitrianti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The study is conducted to learn direct and indirect connections from utility, financial attitude and social capital to fraud management efforts in boalemo district. The study USES a quantitative method. The methods of data collection used in the study are carried out through field observations, questionnaires, interviews, documentation and literature studies. As for the population in this study are all over the bumde administration in boalemo district with a sampling withdrawal using sampling clusters. The data analysis techniques used in research are the structur models (shem) with the help of the smart PLS 3.0 program. The results of the study indicate that (1) fraud fraud effects affect social capital significantly, (2) the financial attitude affects its social capital, (3) fraud prevention efforts, (4) the financial attitude does not significantly affect fraud prevention efforts, (5) social capital does not significantly affect fraud prevention efforts, (6) fraud prevention effects do not significantly affect fraud prevention efforts through social capital (7) financial attitude does not affect fraud prevention efforts through social capital.